2003
DOI: 10.1034/j.1601-183x.2003.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenic C57BL/6 µ opiate receptor (MOR) knockout mice: baseline and opiate effects

Abstract: Homozygous m-opioid receptor (MOR) knockout (KO) mice developed on a chimeric C57B6/129SV background lack morphine-induced antinociception, locomotion and reward. Therefore it appears that MOR largely mediates these morphine actions. However, one factor that could affect the extent of knockout deficits in morphine-induced behavior is the genetic background against which the gene deletion is expressed. To examine the effect of genetic background chimeric C57B6/129SV MOR knockout mice from the 15th generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…Since the behaviorally relevant diffusional spread occurring in the conditions of this study can be estimated as 600 mm laterally and 800 mm dorsally to the injection site, VTA opioid receptors are likely to be the main target of the drug (David and Cazala, 1994a, b). These results are consistent with the previous pharmacological and genetic studies supporting an involvement of MORs in opiate reward (Matthes et al, 1996; Bardo, 1998; Shippenberg and VTA opioid receptors, reward and fos protein expression V David et al Elmer, 1998;van Ree et al, 1999;Chefer et al, 2003;Hall et al, 2003). Although preferentially a m-agonist, morphine also binds DORs with sub-mM affinity.…”
Section: Discussionsupporting
confidence: 89%
“…Since the behaviorally relevant diffusional spread occurring in the conditions of this study can be estimated as 600 mm laterally and 800 mm dorsally to the injection site, VTA opioid receptors are likely to be the main target of the drug (David and Cazala, 1994a, b). These results are consistent with the previous pharmacological and genetic studies supporting an involvement of MORs in opiate reward (Matthes et al, 1996; Bardo, 1998; Shippenberg and VTA opioid receptors, reward and fos protein expression V David et al Elmer, 1998;van Ree et al, 1999;Chefer et al, 2003;Hall et al, 2003). Although preferentially a m-agonist, morphine also binds DORs with sub-mM affinity.…”
Section: Discussionsupporting
confidence: 89%
“…However, these increases were far smaller than might be anticipated from the reduction in their receptor-binding sites (Table 1), suggesting spare receptors. A similar lack of correlation between the receptor density and analgesic response was previously observed in heterozygous mice from Oprm1 KO mouse lines (33,34).…”
Section: Targeting Intracellular Carboxyl Termini Of the Mu Opioid Rementioning
confidence: 54%
“…This was particularly interesting in view of the lack of change in morphine analgesia among the truncation models, despite receptor binding decreases of 30% to 50% in mE4M and mE3M models. Maintaining analgesic activity with reduced receptor expression has been reported previously in mu receptor KO models in which loss of half the receptor in the heterozygotes failed to change morphine's analgesic ED 50 values (33,34). Removal of the exon 4-encoded 12 aa in mMOR-1, the predominant 7TM variant, facilitated morphine tolerance in mE4M homozygous mice on both B6 and 129 backgrounds, implying that expression of the exon 4-encoded sequence impedes the development of morphine tolerance.…”
Section: Discussionmentioning
confidence: 95%
“…In spite of intensive study, the causative genetic variation that underlies Mop2 has yet to be identified. Oprm knockout mice on the B6 genetic background exhibit lack of morphineinduced analgesia, locomotor activity, and conditioned place preference (Hall et al, 2003). Oprm knockout mice have also been shown to lack robust responsiveness in intracerebroventricular morphine self-administration studies (Becker et al, 2000); however, this latter study did not control for genetic background and did not test responsiveness of knockout mice in a voluntary drinking paradigm.…”
Section: Discussionmentioning
confidence: 77%